Ethnopharmacological survey of medicinal plants in Maden (Elazig-Turkey) - Cakilcioglu, Ugur; Khatun, Selima; Turkoglu, Ismail; Hayta, Sukru (Elsevier Ireland Ltd, 2011)
Aim of the study: This study aimed to identify wild plants collected for medical purposes by the local people of Maden County, located in the Eastern Anatolia Region of Turkey, and to establish the uses and local names of these plants. Materials and methods: Field study was carried out over a period of approximately 2 years (2008-2010). During this period, 131 vascular plant specimens were collected. Demographic characteristics of participants, local plant names, utilized parts and preparation methods of the plants were investigated and recorded. In the scope of the study, the plant species were collected: herbarium materials were prepared; and the specimens were entitled. The Zazas are of the major ethnic group in the region. In addition, the relative importance value of the species was determined and informant consensus factor (FIC) was calculated for the medicinal plants included in the study. Results: A total of 88 medical plants belonging to 41 families were identified in the region. 4 plants out of 88 were recorded to be used for curative purposes for the first time. It was determined that the local names of four different kinds of plants used in Maden were same as the different kinds of plants used in different regions. The most encountered medicinal plant families were Urticaceae (>21%), Rosaceae and Lamiaceae (>17% of use-reports), Asteraceae (>13%), Fabaceae (>8%), Brassicaceae (>7%), Poaceae (>4%); the most common preparations were decoction and infusion. Mentha spicata L subsp. spicata, Rosa canina L and Urtica dioica L was the plants most used by the local people. Anthemis wiedemanniana Fisch. and Mey., Bunium paucifolium DC. var. brevipes (Freyn & Sint.) Hedge & Lam., Tchihatchewia isatidea Boiss., Thymus haussknechtii Velen. were found to be the endemic plants used for medical purposes in Maden, Turkey. The medicinal uses of Bunium paucifolium DC. var. brevipes (Freyn & Sint.) Hedge & Lam., Hippophae rhamnoides L subsp. caucasica Roussi, Gladiolus atroviolaceus Boiss., Ixiolirion tataricum (Pallas) Herbert subsp. montanum (Labill.) Takht. were recorded for the first time. Conclusion: Herbal treatment has become a tradition for the residents of the study region. These plants, which are used in the treatment of many diseases. Comparison of the data obtained in this study from the plants growing in Maden with the experimental data obtained in the previous laboratory studies proved most of the ethnobotanical usages. Literature review showed that curative plants of Maden are used in different parts of the world in the treatment of the same or similar diseases. If a plant is used to treat the same disease in different places across the world then its pharmacologic effect could be accepted. It would be beneficial to conduct pharmacologic studies on such plants. These plants, used in the treatment of many different diseases, are in this region at abundant amounts. Drying enabled local people to use medicinal plants during all seasons of the year. This study identified not only the wild plants collected for medical purposes by local people of Maden County in the Eastern Anatolia Region, but also the uses and local names of these plants. It is tried to generate a source for persons studying in ethnobotany, pharmacology and chemistry sciences by comparing knowledge gained from traditionally used herbs with previous laboratory studies. Crown Copyright (C) 2011 Published by Elsevier Ireland Ltd. All rights reserved.
Keywords: Ethnobotany; Medicinal plants; Traditional medicine; Traditional uses; FIC; UV; Maden; Turkey